Confirmation of the Drug–drug Interaction Potential between Cobicistat-boosted Antiretroviral Regimens and Hormonal Contraceptives. Issue 8 (November 2019) - Majeed, Sophia R; West, Steve; Ling, Kah Hiing; Das, Moupali; Kearney, Brian P
Background: Cobicistat (COBI), a CYP3A inhibitor, is a pharmacokinetic enhancer that increases exposures of the HIV protease inhibitors (PIs) atazanavir (ATV) and darunavir (DRV). The potential drug interaction between COBI-boosted PIs and hormonal contraceptives, which are substrates of intestinal efflux transporters and extensively metabolized by CYP enzymes, glucuronidation and sulfation, was evaluated. Methods: This was a Phase I, open-label, two cohort ( n =18/cohort), fixed-sequence study in healthy females that evaluated the drug–drug interaction (DDI) between multiple-dose ATV+COBI or DRV+COBI and single-dose drospirenone/ethinyl estradiol (EE). DDIs were evaluated using 90% confidence intervals of the geometric least-squares mean ratios of the test (drospirenone/EE+boosted PI) versus reference (drospirenone/EE) using lack of DDI boundaries of 70–143%. Safety was assessed throughout the study. Results: 29/36 participants completed the study. Relative to drospirenone/EE alone, drospirenone area under the plasma concentration versus time curve extrapolated to infinity (AUCinf ) was 1.6-fold and 2.3-fold higher, and maximum observed plasma concentration (Cmax ) was unaltered, upon coadministration with DRV+COBI and ATV+COBI, respectively. EE AUCinf decreased 30% with drospirenone/EE + DRV+COBI and was unchanged with ATV+COBI + drospirenone/EE, relative to drospirenone/EE alone. Study treatments were generally well tolerated. The majority of adverse events were mild and consistent with known safety profiles of the compounds. Conclusions: Consistent with COBI-mediated CYP3A inhibition, drospirenone exposure increased following coadministration with COBI-containing regimens, with a greater increase with ATV+COBI. Thus, clinical monitoring for drospirenone-associated hyperkalaemia is recommended with DRV+COBI and ATV+COBI should not be used with drospirenone. Lower EE exposure with DRV+COBI may be attributed to inductive effects of DRV on CYP enzymes and/or intestinal efflux transporters (that is, P-gp) involved in EE disposition.